Inside Back Cover: Wavefunction in Density Functional Theory Embedding for Excited States: Which Wavefunctions, which Densities? (ChemPhysChem 15/2014). Issue 15 (20th October 2014) - Daday, Csaba; König, Carolin; Neugebauer, Johannes; Filippi, Claudia
<x xml:space="preserve">Abstract</x> Embedding a wave function in density functional theory raises the question of which methods to combine in computing the excitation energies, which depend on the embedding potential and its barriers, as presented on p. 3205 by J. Neugebauer, C. Filippi et al.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>